Improving the root system of apple rootstocks based on Agrobacterium rhizogenes-mediated transformation system - Yushuang Guo; Zijun Wang; Cecilia H. Deng; Jianjun Dong; Shiqi Shu; Yi Wang; Zhenhai Han; Wei Li (Fruit Research)
Dwarfing and close planting have become the general trend of the apple industry, but the rooting difficulty of dwarfing rootstocks has seriously limited efficient breeding. Agrobacterium rhizogenes can infect plants and induce the formation of hairy roots. In this study, the optimal A. rhizogenes-mediated transformation system was explored for three apple rootstocks: 'M9', 'M26', and Malus xiaojinensis. The results reveal that the best transformation concentration for all three rootstocks is OD600 of 0.5. 'M9' and 'M26' exhibited rooting rates of 86.08% and 89.96%, respectively, upon transformation with A. rhizogenes strain K599. In contrast, M. xiaojinensis attained a rooting rate of 90.97% when strain MSU440 was introduced. Furthermore, a Cytokinin Oxidation/Dehydrogenase (CKX) gene was demonstrated to significantly increase the root length and lateral root density of hairy roots. These results have the potential to enhance the rooting ability of dwarfing rootstocks and contribute to the development of more efficient and productive orchard management strategies.